SPEAKING STUDENTS’ WORKSHEET BASED ON E-BOOK: English - Romayanti Dewi; Mai zuniati (Prodi Tadris Bahasa Inggris, 2021)
ABSTRACT Digital books or e-books (electronic books) are one of the technologies that utilize computers that are used to display information in the form of text, images, audio, video, and other multimedia in a concise and dynamic form that can be read by computers or other electronic devices. This type of research is Research and Development (R&D) with a 4D model (Define, Design, Develop, and Disseminate). Define phase to define problems in learning. Design phase to produce initial products and research instruments. The develop phase to obtain product and instrument eligibility. Disseminate stage for the distribution of teaching materials based on e-books. Research instruments include: validation sheets, and response questionnaires. The results showed that e-book based teaching materials were appropriate to be used to increase the interest of students in MA Ma'arif Roudlotu Tholibin in terms of expert assessments with good categories and from the responses of students and teachers in very good categories. From the assessment of language, materials and media that is 69%, 64% and 72% with good evaluation criteria. Whereas for students of MA Ma'arif Roudlotu Tholibin that is 87% with criteria very good and the teacher is 87% with very good criteria.